Higher Cortisol Level Would Increase the Risk of Spontaneous Abortion - Sastra, Christian (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To understand the correlation between cortisol level and spontaneous abortion in normal pregnancy with gestational age less than 20 weeks. Method: The study design was a correlative analytic prospective study with cross sectional observational approach. This study started from June 2012 until the number of participant sufficiently from Prof. Dr. R.D. Kandou General Hospital. The data then processed SPSS version 2.0, ROC and logistic regression equation model (chance model). Result: The study included 50 cases consisted of 25 spontaneous abortion cases and 25 normal pregnancies with gestational age less than 20 weeks, and got result if cortisol level for 18.52 Î¼g/dl so spontaneously abortion chance for 35.7% and if cortisol level for 24.0 Î¼g/dl would chance for spontaneous abortion for 99.3%. Conclusion: In this study, there was a significant difference in cortisol level in women with spontaneous abortion and < 20 weeks normal pregnancy. Higher cortisol level would increase spontaneous abortion risk. The mean cortisol level in spontaneous abortion was 27.28892 Î¼g/dl. While the mean cortisol level in women with normal pregnancy was 11.7660 Î¼g/dl. Analysis of the correlation between cortisol level and spontaneous abortion gave a cut off point for cortisol level of 19.1 Î¼g/dl with sensitivity of 92% and specificity of 92%. [Indones J Obstet Gynecol 2013; 37-1: 17-20] Keywords: cortisol level, normal pregnancy, spontaneous abortion